A pathway to local legitimacy: the impact of corporate governance on corporate social responsibility in chaebol-affiliated firms - Chune Young Chung; Hoje Jo; Junyoup Lee (Financial Innovation)
Abstract Drawing on local legitimacy theory, which posits that firms seek acceptance and approval from their local community and stakeholders, we examine the effect of corporate governance (CG) quality on corporate social responsibility (CSR) activities in Korea. Enhancing CG quality and engaging in CSR activities are increasingly important for firms’ long-term sustainability. Using the KEJI-CSR index and the KCGS CG score, we find that CG quality positively influences CSR activities. Specifically, if the CG quality score increases by one standard deviation, CSR improves by approximately 1.6–2.3% of the mean CSR score. Furthermore, the relationship between CG and CSR is stronger for business conglomerates (chaebol-affiliated firms), suggesting that sound CG practices can promote CSR activities more effectively when the interests of management and stakeholders are better aligned. This finding supports local legitimacy theory. Our findings are robust under various tests, including difference-in-differences analysis and propensity score matching. An interesting policy implication is that multinational enterprises or foreign investors should prioritize the CG quality of their local subsidiaries or investee firms. Better CG practices can enhance CSR activities, which are essential for long-term survival in local markets. This study, however, is limited to Korea and may not be generalizable to other emerging markets with different governance structures.